PEMISAHAN HARTA BERSAMA PADA POLIGAMI DIBAWAH TANGAN (STUDI KASUS DI DESA TEBING LESTARI KABUPATEN KAMPAR) - Elpiya '; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Marriage in Indonesia under the Act is based on monogamous marriage but not limiting. Marriages taking place not only marriage one husband with one wife, although in principle it was. Problems will occur when there is no division of joint property. The authors found that polygamy divorces occurred in the village of Cliffs Lestari no division of community property between husband and ex-wife of former poligaminya both religious law and customary law, so the former wife of polygamy did not get a part of the joint property. The second is based on the author intends to examine the differences in the form of a thesis with the title "Separation of Assets Together In Polygamy Under Hand Case StudiesofSustainableCliffsVillagKampar". The purpose of this research is: To find out the separation of joint property on hand in the village of polygamy under Cliffs Lestari Kampar district. Knowing for efforts to be made by the wife who practice polygamy under the hand if it does not get joint property. The division of joint property in polygamous marriages under the hand has some constraints, namely because this marriage is not regulated by legislation so as to make a claim to the religious court is highly unlikely, Indigenous legal settlement does not run smoothly because customarylawsdonot'mstrictlyadheredto. The conclusion of these problems is the first: The division of joint property on divorce polygamy can use Customary law. The second attempt to do if the wife does not get a piece of common property in the village perceraiann Cliffs sustainable polygamy in Kampar is to use Customary law for mengungat the husband to the district court. As for the suggestion of the author is division of joint property on divorce polygamy under arms in the village of Cliffs sustainable Kampar district shall in dilakuan the Customary law.Keywords: Polygamy under the hand - Joint Distribution Assets - Islamic Law